Sonification of single-walled carbon nanotubes properties for engineering applications. (9th April 2020) - Shakhnov, V.A.; Chernyshov, V.N.; Zinchenko, L.A.; Tyutin, A.K.; Kazakov, V.V.
In the paper, we discuss some approaches to sonification in nanoengineering applications. We review sonification techniques and then discuss their applications in nanoengineering. We consider sonification of electrical properties of single-walled carbon nanotubes and random carbon nanotubes networks as our use cases. Finally, we discuss advantages of sonification in nanoengineering.